Healable, recyclable, and adhesive rubber composites equipped with ester linkages, zinc ionic bonds, and hydrogen bonds. (April 2022) - Yang, Li; Wu, Mingliang; Yang, Xueli; Lin, Baofeng; Fu, Lihua; Xu, Chuanhui
Graphical abstract: Abstract: This study reports healable, recyclable, and adhesive rubber composites equipped with ester linkages, Zn 2+ ionic bonds, and H-bonds based on carboxylic styrene butadiene rubber (XSBR), nano-ZnO, and diglycidyl ether of bisphenol A (DGEBA). Zn 2+ ionic cross-links are introduced into XSBR networks through the acid-base reaction between nano-ZnO and carboxyl groups of XSBR. The in-situ generated Zn 2+ is thus evenly dispersed in the rubber matrix to serve as transesterification catalyst, which promotes the healing and reprocessing of the rubber composites at a higher temperature. The healing efficiency of the rubber composites can realize 75% and further improved to 90% after introducing additional hydroxyl groups. The rubber composites can reprocess at least 5 times. Moreover, the rubber composites are easily disintegrated to recycle neat XSBR due to the dissociation of ester linkages in the alkaline solution. Interestingly, the rubber composites show a surprising reversible adhesion property under water stimulation.